If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + b + -45 = 2a + 4b + 465.23 + a + 103b Reorder the terms: -45 + 3a + b = 2a + 4b + 465.23 + a + 103b Reorder the terms: -45 + 3a + b = 465.23 + 2a + a + 4b + 103b Combine like terms: 2a + a = 3a -45 + 3a + b = 465.23 + 3a + 4b + 103b Combine like terms: 4b + 103b = 107b -45 + 3a + b = 465.23 + 3a + 107b Add '-3a' to each side of the equation. -45 + 3a + -3a + b = 465.23 + 3a + -3a + 107b Combine like terms: 3a + -3a = 0 -45 + 0 + b = 465.23 + 3a + -3a + 107b -45 + b = 465.23 + 3a + -3a + 107b Combine like terms: 3a + -3a = 0 -45 + b = 465.23 + 0 + 107b -45 + b = 465.23 + 107b Solving -45 + b = 465.23 + 107b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-107b' to each side of the equation. -45 + b + -107b = 465.23 + 107b + -107b Combine like terms: b + -107b = -106b -45 + -106b = 465.23 + 107b + -107b Combine like terms: 107b + -107b = 0 -45 + -106b = 465.23 + 0 -45 + -106b = 465.23 Add '45' to each side of the equation. -45 + 45 + -106b = 465.23 + 45 Combine like terms: -45 + 45 = 0 0 + -106b = 465.23 + 45 -106b = 465.23 + 45 Combine like terms: 465.23 + 45 = 510.23 -106b = 510.23 Divide each side by '-106'. b = -4.813490566 Simplifying b = -4.813490566
| 13-x/7=-1 | | -1/5a+7=(-11) | | (x+2x+5)-10=22 | | 5/8x24 | | a/b-45=2a+4b+465.23+a+103b | | 1/4(8x-16)=6x+2 | | ab-45=2a+4b+465.23+a+103b | | -15-(-8)+7= | | ab-45=2a+4b+465.23+a+103ab | | -1-6k=-7k-19 | | 2+25p^2=66 | | 10a+15a=75 | | 2x+6=-6x-34 | | -7s+4=-7-8s+4 | | 6-7i/6+7i | | 60=-5x+10 | | 8v+35=7(6v+5) | | (1/2x)=32 | | 2g-14=g | | 4(y+2)=15 | | ab-45=2a+4b+465.23+a | | 156/180=x/120 | | (1-2x)=32 | | 13x-68=-7x+12 | | (1/3*9)3 | | 3x+26/5=7 | | n+3n=180 | | 0.8(m+4)-0.3m= | | 5x=-6x-22 | | -6-j=4+j | | -27=-2x-7 | | -p-4=-12 |